The Existence of Local Culture of the Indigenous People of Negeri Lohiatala in the Era of Modernization - Titaley, Elsina; R. Alfons, Christwyn (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
Negeri is a territorial area of Indigenous peoples who built an everyday life long ago to form an identity kinship relationship. This research aimed to analyze the local culture of the indigenous people of Negeri Lohiatala-Seram Island in the era of modernization. The reality shows that the knowledge of indigenous peoples about the local traditions of indigenous peoples has relatively disappeared in the indigenous lands in Maluku. It is seen in the need forty's lack of knowledge, especially the current generation, of various traditions and customs of local communities created by ancestors in the past. Identifying, and finding the problem of low knowledge of local traditions and customs is a solution step currently being taken to maintain the local values of indigenous peoples in the archipelago in the era of modernization. Indeed, the effort aims to maintain the existence of the rich local cultures of indigenous peoples in the islands. The location determined to conduct an exploration described above was Negeri Lohiatala in the West Seram Regency administrative area. The method used is qualitative research. It is expected that by using this method, the data search process can be optimized in depth so that phenomena related to the problem under study can be revealed. The results of this research are expected to try to maintain the local traditions of the Indigenous people of Negeri Lohiatala and become a file project for other Indigenous Negeri in the archipelago of Maluku in particular and Indonesia in general.